1999
DOI: 10.1097/00007632-199906010-00009
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Adaptation of the Roland-Morris Questionnaire for German-Speaking Patients With Low Back Pain

Abstract: Because the German version of the Roland-Morris Questionnaire seems to be reliable and valid for the assessment of the functional status in German-speaking patients with low back pain, the use of this translated instrument can be recommended in future clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
99
1
15

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(131 citation statements)
references
References 26 publications
16
99
1
15
Order By: Relevance
“…The adaptation of the RMDQ for the Tunisian language has produced an instrument that is reliable and demonstrative of both internal and external validities. Reliability levels were similar to the French [4], German [22], Italian [15], Spanish [11] and Turkish [12] versions. Although statistically significant, the correlation in our study of the RMDQ score with the Schober test and the pain visual analogue scale is weak, compared with the original version [16] and the Italian version [15], for which correlation of the RMDQ score with the pain visual analogue scale was very good (r=0.79; P<0.001).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The adaptation of the RMDQ for the Tunisian language has produced an instrument that is reliable and demonstrative of both internal and external validities. Reliability levels were similar to the French [4], German [22], Italian [15], Spanish [11] and Turkish [12] versions. Although statistically significant, the correlation in our study of the RMDQ score with the Schober test and the pain visual analogue scale is weak, compared with the original version [16] and the Italian version [15], for which correlation of the RMDQ score with the pain visual analogue scale was very good (r=0.79; P<0.001).…”
Section: Discussionsupporting
confidence: 52%
“…The Roland-Morris Disability Questionnaire (RMDQ) [16] (Appendix) is the most common instrument used, and studies have reported that the test/re-test reliability, validity and responsiveness of RMDQ are adequate [16,18]. Furthermore, it has been successfully adapted across cultures [11,12,15,22]. The purpose of this study is to validate the culturally adapted, Tunisian-language version of the RMDQ.…”
Section: Ismail Bejia Mohamed Younes Ben Sallem Kamel Mondher Letaiefmentioning
confidence: 99%
“…1, 2, 3). At the follow-up visit the German version of the Roland-Morris score (0=no back-painrelated disability; 24=maximum back-pain-related disability) was applied to evaluate the patient-perceived disability caused by back pain [20] and the current neurological status was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Te sto wa nie kwe stio na riu sza Zgod ność we wnętrz ną kwe stio na riu sza dla na rzę -dzi sa mo oce ny wy zna cza się przez po rów na nie wyni ków uzy ski wa nych za po mo cą te go kwe stio na riusza wy peł nia ne go dwu krot nie [22]. W ce lu oce ny zgod no ści we wnętrz nej, gru pa 20 pa cjen tów wy peł -ni ła kwe stio na riusz dwu krot nie w od stę pie jed ne go dnia.…”
Section: Translation and Cross-cultural Adaptationunclassified
“…Traf ność kon struk cji na rzę dzia ba daw cze go ocenia się przez po rów na nie wy ni ków uzy ski wa nych przy po mo cy oce nia ne go na rzę dzia ba daw cze go oraz na rzę dzia uzna ne go za re fe ren cyj ne [22]. W ce lu oceny traf no ści, w dru giej fa zie ba da nia, kwe stio na riusz te sto wa no na 61 ko lej nych pa cjen tach Kli ni ki le czonych z po wo du or to pe dycz nych scho rzeń sto py i stawu sko ko we go.…”
Section: Translation and Cross-cultural Adaptationunclassified